2023
DOI: 10.3390/ijms24021441
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cucurbiturils on the Production of Reactive Oxygen Species by T- and B-Lymphocytes, Platelets and Red Blood Cells

Abstract: Reactive oxygen species (ROS) are highly reactive chemical molecules containing oxygen. ROS play an important role in signaling and cell homeostasis at low and moderate concentrations. ROS could be a cause of damage to proteins, nucleic acids, lipids, membranes and organelles at high concentrations. There are a lot of cells that can produce ROS to maintain functional activity. It is known that metal nanoparticles can increase production of ROS in cells. However, the effect of cucurbiturils on ROS production is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, we evaluated the possible immunomodulatory effect of cucurbiturils [ 30 , 31 , 32 , 33 ], and it was shown that during cultivation in the presence of CB[n], the proliferative activity of cells increased and the expression of HLA-DR on lymphocytes increased, which indicates an immunostimulatory effect. It was shown that cucurbiturils had practically no immunosuppressive effect under in vitro conditions, except for a slight decrease in HLA-DR expression and the production of reactive oxygen species by T-helpers in stimulated cultures [ 30 , 33 ]. However, for macrocyclic cavitands and for cucurbiturils it has been demonstrated that some properties only manifest themselves under in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we evaluated the possible immunomodulatory effect of cucurbiturils [ 30 , 31 , 32 , 33 ], and it was shown that during cultivation in the presence of CB[n], the proliferative activity of cells increased and the expression of HLA-DR on lymphocytes increased, which indicates an immunostimulatory effect. It was shown that cucurbiturils had practically no immunosuppressive effect under in vitro conditions, except for a slight decrease in HLA-DR expression and the production of reactive oxygen species by T-helpers in stimulated cultures [ 30 , 33 ]. However, for macrocyclic cavitands and for cucurbiturils it has been demonstrated that some properties only manifest themselves under in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%